(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
Chemical pesticides of different groups have been tested against crucifer crop damaging beetles with the aim of introduction of modern formulations. As a result of two-year research it was found out that the biological efficiency of tested formulations Calypso (0.1 L/ha), Confidor (0.1 L/ha) and Karate Zeon (0.3 L/ha) against crucifer beetles in 10 days after spraying made 95.7–99.4%.